Hierarchical chabazites synthesized by combining primary and secondary structure-directing agents - Marins, Natália Hadler [UNESP]; Feliciano Pereira, Elen Maria [UNESP]; Alahakoon, Sandamini H.; Huang, Yining; Martins, Leandro [UNESP] (Elsevier, 2022)
Modifying the physical and chemical properties of zeolites by altering the synthesis parameters or using post-synthesis treatments may offer additional properties other than those that make them widely used materials. Remarkably, the chabazite SSZ-13 zeolite possesses a small pore opening that provides access to a large cavity, making the structure suitable for converting methanol to products. Herein, we altered the porosity of SSZ-13 by adding various amounts (2, 4, and 8% in relation to the molar silica content) of dimethyloctadecyl[3-(trimethoxysilyl)propyl] ammonium (DMOAP) into the reaction mixture. The introduction of DMOAP enabled the formation of the pure chabazite structure without affecting the incorporation of aluminum atoms into the zeolite framework. At the same time, its incorporation led to changes in porosity, increasing the external surface area and creating mesopores without affecting the formation of micropores. Concerning the catalytic conversion of methanol into products at low temperatures (210 °C), the additional porosity decreased the methanol to dimethyl ether conversion, indicating that the confinement effect plays an essential role in stabilizing the reaction intermediates. However, at higher temperatures (400 °C), the mesopores played an essential role in the methanol to olefins reaction by increasing the catalyst lifetime and the conversion over time due to improved accessibility of methanol to reaction intermediates confined in the micropores.
Keywords: Crystallization under tumbling conditions; DMOAP; Hierarchical zeolites; Mesoporous zeolites; SSZ-13